MICRO-ADVANCEMENT OF ORGANIZATIONAL BEHAVIOR IN MANAGEMENT. INDIVIDUAL AND COMMUNITY - Asimova, Feruza Abdusattorovna; Zagidullina, Kamila Rafailovna (THE INNOVATION ECONOMY, 2026)
In organizational behavior, individuals become subjects of control. Only by reaching the highest levels of the organizational hierarchy can employees hope for a reduction in pressure from management, but these hopes are not always realized. Thus, organizational behavior and management are closely interrelated. The subject of control always determines the fundamental formal laws of organizational behavior. This was especially evident in the industrial era.